Pengembangan Media Papan Baca Pintar Berbasis Literasi Sains di SDN 011 Tarakan - Kadek Dewi Wahyuni Andari; Agustinus Toding Bua; Dinda Oktaviani (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2020)
The aims of this research to develop learning media that can help students improve reading and writing skills. This research and development also helps teachers to make learning media easy and fun for students. The type of this research that is research and development. This research and development model refers to the Research and Development (R&D) stage proposed and modified by Borg and Gall. This research and development stage consists of nine stages: (1) potential and problems, (2) information gathering, (3) product design, (4) design validation, (5) design improvement, (6) product trials, (7) product revisions, (8) trial use, (9) product revisions. Data collection instruments used were, observation, interviews, validation sheets and student questionnaire responses. The results of smart reading board media research obtained from validation sheets and student questionnaire responses were said to be feasible. Based on the assessment conducted by media experts obtained an average score of 4 with a percentage of 95% and material experts with a percentage of 90%. Then the questionnaire responses of students in the trial use reached 100%. Based on the acquisition of the average score and percentage, the learning media of smart reading boards based on scientific literacy on the environment around my house, is said to be feasible to use.